RETRACTED: Straticyte demonstrates prognostic value over oral epithelial dysplasia grade for oral potentially malignant lesion assessment. (September 2017) - Hwang, Jason T.K.; Gu, Ying R.; Dickson, Benjamin J.; Shen, Mi; Ralhan, Ranju; Walfish, Paul G.; Mock, David; Pritzker, Kenneth P.H.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. We have recently been made aware that the sensitivity values and the false-negative values reported in the manuscript were erroneous. The sensitivity values were reported as 71% and 60% in the article, but it was later determined that they were 48% and 36%, and the false-negative value was reported as 6 in the article but was 16. The Editors have determined that the values have changed so greatly that the conclusions of the paper can no longer be supported.